NILAI-NILAI SOSIAL DALAM NOVEL TING! KARYA PRIYANTO CHANG: PENDEKATAN SOSIOLOGI SASTRA - Indah Purnama Sari; Nurhayati Harahap (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
In a literary work such as a novel, of course there are social values in social life. These values in social life develop into social values that require sociological studies such as in a literary work in the form of a novel entitled "Ting!". This article aims to describe the social values contained in the novel “Ting!” by Priyanto Chang. The research method used is a qualitative research method with an analysis of the sociology of literature approach. The application of this qualitative method is descriptive, which means that the data generated is in the form of words in the form of quotations. The results of this study indicate that the novel "Ting!" Priyanto Chang's work has social values, including: 1) the value of compassion, consisting of devotion, mutual help, loyalty, and caring. 2) the value of responsibility, consisting of a sense of belonging and empathy. 3) the value of harmony in life, consisting of tolerance and cooperation.